Research on Performance of a Kind of Compound-type Corrosion-Inhibition Bactericide. (October 2019) - Changshan, Huang; Jinying, Wu; Min, Chen; Huiwu, Xu; Min, Zhang; Mian, Xue; Xiaoguang, Zhang
Abstract: In the experiment, rotative weight loss method, electrochemical polarization, MPN, etc. were used to investigate the corrosion inhibition and bactericidal performance of compound-type corrosion-inhibition bactericide composed of phosphono-, carboxyl quaternary ammonium salt, etc. on A3 carbon steel in industrial recycling cooling water. The experimental test results showed that when the content of compound agentia reached 100 mg. L −1, the corrosion rate of it on A3 carbon steel was 0.0366 mm. a −1, superior to relative standard regulations, less than 0. 075mm.a −1 . While metallographic-phase microscopy test showed that there is a layer of protective film on the surface of A3 carbon steel, which indicated that compound agentia had relatively better corrosion-inhibition effect on A3 carbon steel; when the content of compound agentia reached 80-100 mg. L −1, the sterilizing rate of compound agentia on heterotrophic bacterium and sulfate reducing bacteria were up to more than 99%, which indicated that compound agentia had good bactericidal performance.